Analysis of Three Potential Savings in E-Working Expenditure - Beno, Michal (Frontiers in Sociology, 2021)
The aim of this research study is to contribute to the sustainability of e-working initiatives, specifically by exploring three employee-financial impacts. The study adopted a two-step methodological approach: firstly, a comprehensive review of the existing literature was done and, secondly, secondary data analysis was carried out. The study analyses how three potential financial benefits for e-workers differ in various countries and whether these can increase e-workers’ earnings. It was found that there are significant benefits. Regarding the affordability of a home, e-working presents a useful tool to move to less costly regions. This reduces the struggle with housing. Aside from housing, commuting is one of the largest time and cost consuming expenses. Based on our calculations, all employees can save commuting time and money by using public transport or their own vehicles. Important considerations here are the costs, such as fuel, insurance, tolls, time, health and environment. Making cappuccino or coffee at home is a useful way to decrease expenses compared to buying them at a café. Generally, the results indicate that an increase of e-working tends to decrease selected expenses of employees. This paper point outs that, on the basis of average costings, e-working decreases selected expenses of employees. The findings also indicate that more long-term and comprehensive studies are needed, especially in relation to other benefits, such as lunch, childcare and clothing. This study has contributed to highlighting the e-working financial benefits for e-workers by not commuting to work.